Using outcome measures in child protection work. Issue 3 (6th December 2020) - Hood, Rick; Lansley, Sue; Mitchell, Toni; Gaskell‐Mew, Elaine
Abstract: While many evidence‐based tools and measures exist to support child protection practice, in the United Kingdom, there is little evidence of their routine use in casework. This paper reports on a qualitative study exploring the use of such tools with children and families receiving statutory social care services. Fifteen social workers working in child safeguarding teams in two local authorities in Southeast England agreed to incorporate the use of outcome measures into their casework over a 6‐month period. Qualitative data were collected through monthly action learning workshops held separately in each local authority. The results showed how the impact of using the measures was shaped by a combination of institutional factors, practice context and the dynamics of casework. Outcome measures were found to have benefits as well as limitations with respect to partnership working, assessment and decision‐making and overall social work practice. Implications are discussed for the prospects of enhancing the use of evidence‐based tools in statutory social work with children and families.